Nova ureditev omejitve ustanavljanja družb in podjetnikov, pridobitve statusa družbenika ter prenehanja gospodarskih družb - Bratina, Borut (Podjetje in delo, 2015)
Amendment to the Slovenian Companies Act from year 2011 (ZGD-1E) had brought inappropriate and severe restrictions regarding establishing, managing and supervising of companies for individuals who were active at one of these positions in companies subject to insolvency proceedings. The Constitutional Court of the Republic of Slovenia has repealed the disputed provisions of Articles 10a and 10b of the Companies Act. However, the latest amendment to the Companies Act (ZGD-1I) represent a better solution for restrictions in the sphere of establishing of companies and acquiring shareholder status. The restrictions are limited to persons who had been convicted for some criminal offences and their judgments are final, failure to pay tax obligations and failure to submit tax returns to the authorities, multiple penalties for non-payment of work remuneration or other offences, e.g. undeclared work, deletion from the court register without liquidation and multiple limited liability company establishment or acquiring of a share in a limited liability company in the last three months. These restrictions apply prospectively and do not interfere with legally established states in companies.
Keywords: delničarji; družbeniki; gospodarske družbe; gospodarsko pravo; prenehanje; ustanovitev